Development of a New Primary School English Curriculum and Textbooks in Myanmar - Hall, James M; Gaynor, Brian (TESL-EJ (Berkeley, Calif.), 2020)
This article reports on the design and implementation of an innovative primary EFL program in Myanmar. Begun in 2014, the program is part of the CREATE Project, a joint initiative between the Myanmar Ministry of Education and the Japan International Cooperation Agency (JICA). The project has involved the planning, designing and implementation of a new curriculum for primary school English, along with concurrent materials development and the design of both pre-service and in-service teacher training courses. To give an insight into this multifaceted process, this paper focuses on the development of the Grade 3 textbook and compares it to the former book. After this analysis, it considers teachers' needs and the challenges they face through analyzing posts and comments made on the "New Curriculum English Subject" Facebook page. Teachers' primary challenges were learning the new textbook language, incorporating the recommended instruction into their established pedagogical approaches, and time management. The challenges and solutions outlined in this article have both policy and pedagogical implications for curriculum innovation at the primary EFL level, particularly with respect to the issues facing less economically developed countries.